Prediktor Kepemimpinan Mutu dan Mutu Pelayanan Kesehatan di Rumah Sakit - Komala Sari; Mitra Mitra; Jasrida Yunita; Budi Hartono; Dedi Afandi (Politeknik Kesehatan Kemenkes Mamuju, 2020)
Law Republic Indonesia Number 44 of 2009 on Hospitals states health care institutions must improve higher quality and affordable services to highest health level. Quality leadership is continuous work method and process improve service quality, competitiveness and productivity. Health services quality is reference to the ideal level of health services. Hospitals health services quality will be good if the leadership carried out properly. In general hospital there was an absence Performance Report, disintegration and not sinergy between stakeholders in terms of health services quality. There was nothing of a Minimum Services Standards measurement, has not implemented a customer satisfaction based service pattern, service quality has not met national standards, which indicates that service quality is not optimum. Quality control activities not yet implemented, Standard Operational Procedure was also not optimal. Research objective was to know the effect of quality leadership on the quality of health services. Quantitative research type with analytic cross-sectional design. The study conducted in July 2017 in the Outpatient Installation. The population were all medical personnel and health workers with a sample of 100 people. Techniques for collected data using a questionnaire. The variables in this study were exogenous variables of quality leadership and endogenous variables of health services quality. Data analysis used Structural Equation Modeling - Partial Least Square. The results of the study obtained Values, Vision, Inspiration, Innovative, Systems View, Empowering, Customer Focus, were predictors of quality leadership. Professional standards, service standards, codes of ethics and standard operating procedures were predictors of health services quality. The value of T-Statistic 0.669 with a statistical value of 1.96 there was no significant effect of quality leadership on the health services quality.